Modified Bufei decoction improves calf health by enhancing immunity, reducing inflammation, and modulating gut microbiota - Yang, Zhuo; Ji, Peng; Hua, Yongli; Li, Chenchen; Yang, Haochi; Wu, Fanlin; Wang, Xiuqin; Wei, Yanming; Yan, Jianpeng (Frontiers in Veterinary Science, 2025)
ObjectiveTo analyze the active ingredients of Modified Bufei Decoction (MBFD) and their targets of action, as well as to validate the preventive effects of its modified formulation on respiratory diseases in calves.MethodsNetwork pharmacology and molecular docking were employed to identify active components and targets. Sixty calves were randomly allocated to control and MBFD groups (21-day intervention). Pneumonia incidence, serum inflammatory factors, immune parameters, and antioxidant capacity were measured, with gut microbiota analyzed by 16S rDNA sequencing. The Spearman method was used to analyze the correlation between the differential intestinal flora and the total ingredients.ResultsSystematic screening identified 233 bioactive components in MBFD that target key molecules, such as TNF and IL-6, and modulate pathways, including IL-17 and PI3K/AKT. Molecular docking suggests preliminary binding indications between them. There was a 17% reduction in pneumonia incidence with MBFD (43.3%) compared to the control group (60%). Immunoglobulins (IgA, IgG, and IgM) and antioxidants (CAT, GSH, T-SOD, and T-AOC, all with p < 0.05) showed an increasing trend, while inflammatory cytokines (IL-6, TNF-α, and IL-1β) and MDA exhibited a decreasing trend. The predominant phyla identified through 16S rDNA sequencing were Firmicutes, Bacteroidetes, and Proteobacteria. After drug administration, the relative abundance of Bacteroidetes increased compared to the control group.ConclusionMBFD enhances growth, immunity, and intestinal health in calves by modulating the gut microbiota, alleviating dysbiosis, and reducing the incidence of respiratory diseases. This study provides a basis for the rational application of MBFD in calf healthcare.